OPTIMASI RESPONSIVITAS WEB DENGAN PENDEKATAN MOBILE-FIRST DESIGN - Insan Kamil Nurhikmat; Asep Id Hadiana; Fatan Kasyidi (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The rapid growth of mobile device usage for internet access has significantly shifted the approach to web design, with responsive and mobile-first design becoming crucial in web development. This study aims to optimize the user experience of Puskesmas web through mobile-first design. The research questions include strategies for improving performance and efficiency of Puskesmas web, measuring web responsiveness, and optimizing user experience. The research methods include a literature review, user needs analysis, prototype design, testing, data collection and analysis, and report compilation. The expected results are expected to enhance the responsiveness of Puskesmas web on mobile devices, benefiting web developers and users in achieving a better and more optimal experience.